Factors influencing the health behaviors of patients with ischemic stroke from a social-ecological perspective: a cross-sectional study - Min-Xiu Wang; Gui-Zhen Weng; Jin-Hua Liao; Xin-Yan Chen; Yan-Juan Lin (BMC Public Health)
Abstract Background Although numerous studies have investigated factors associated with health behaviors in patients with first-onset ischemic stroke, the variables examined have varied substantially. Moreover, most analyses have employed ordinary linear regression models that treat variables across different levels as equivalent, thereby overlooking the nested structure of influencing factors. To address this methodological limitation, the present study adopts the Social-Ecological Model as a theoretical framework and employs hierarchical linear modeling (HLM) as a statistical approach. This framework enables systematic stratification of factors across individual, interpersonal, community, and societal levels, and facilitates the identification of key level-specific factors associated with health behaviors in this patient population. Methods This cross-sectional study included 350 patients with first-onset ischemic stroke who were assessed via structured telephone interviews three months after hospital discharge. Univariate analysis, correlation analysis, stratified multivariate analysis, and hierarchical linear modeling (HLM) were conducted to identify key factors associated with patients’ health behaviors. Results Stratified multivariate analysis identified educational level, physical functioning, stroke-related knowledge, and health beliefs as individual-level factors; per capita monthly household income and perceived social support as interpersonal-level factors; and community health environment, distance to the hospital, and place of residence as community- and societal-level factors associated with patients’ health behaviors. Further analysis using hierarchical linear modeling (HLM) revealed stroke-related knowledge, health beliefs, and perceived social support as the most salient associated factors across levels. Conclusions Health behaviors among patients with ischemic stroke were shaped by a hierarchically structured set of factors spanning the individual, interpersonal, community, and societal levels. The present study offers a theoretical foundation for informing the development of targeted, multilevel strategies aimed at promoting health behavior improvement in this population.